2017
DOI: 10.1097/md.0000000000006711
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the abnormal diastolic vortex structure and impaired left ventricle filling in patients with hyperthyroidism

Abstract: Intraventricular hydrodynamics plays an important role in evaluating cardiac function. Relationship between diastolic vortex and left ventricular (LV) filling is still rarely elucidated. The aim of this study was to evaluate the evolution of vortex during diastole in hyperthyroidism (HT) and explore the alteration of hydromechanics characteristics with sensitive indexes.Forty-three patients diagnosed with HT were classified into 2 groups according to whether myocardial damage existed: simple hyperthyroid group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The optimized blood flow dynamics can reflect the general function of left ventricle and the ability of cardiovascular system in maintaining the relative stabilization of blood circulation . The change in intra‐ventricular blood flow‐pattern is related to the diastolic filling . Most studies have assessed LVDD and LV diastolic filling by quantitative analysis of intra‐ventricular vortex derived from MRI echo or VFM.…”
Section: Introductionmentioning
confidence: 99%
“…The optimized blood flow dynamics can reflect the general function of left ventricle and the ability of cardiovascular system in maintaining the relative stabilization of blood circulation . The change in intra‐ventricular blood flow‐pattern is related to the diastolic filling . Most studies have assessed LVDD and LV diastolic filling by quantitative analysis of intra‐ventricular vortex derived from MRI echo or VFM.…”
Section: Introductionmentioning
confidence: 99%
“…After stress, the left ventricular blood flow velocity and eddy current increased, especially at D1 and D2; therefore, the D1 and D2 cir were higher than those of the control group. Zhou et al ( 33 ) showed that changes in the diastolic cir and vortex area reflect the abnormal filling of left ventricular diastolic blood flow. Therefore, cir and eddy current area changes can reflect cardiac blood flow changes.…”
Section: Discussionmentioning
confidence: 99%
“…The change of diastolic vortices in the type 2 diabetic patients with early CKD was similar to that in non-CKD patients with diastolic dysfunction. The early diastolic vortex had a small size and weak intensity with no statistical difference, and the late diastolic vortex became significantly stronger in non-CKD patients with diastolic dysfunction [ 29 , 32 ]. Our data further confirmed that the LV filling parameters were closely associated with the behavior of diastolic vortices.…”
Section: Discussionmentioning
confidence: 99%
“…It is calculated by accumulating the velocity component of a tangent on a closed curve, so the circulation becomes higher when the flow velocity is higher [ 29 ]. The area and circulation of the LV largest clockwise vortex during systole (S-vortex), early diastole at the time of E wave (E-vortex), and late diastole at the time of A wave (A-vortex) were recorded as previously described [ 28 ].…”
Section: Methodsmentioning
confidence: 99%